2020
DOI: 10.1111/jdi.13314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of low‐dose liraglutide in weight control among Taiwanese non‐diabetes patients

Abstract: Aims/Introduction Obesity and metabolic syndrome are well‐known to be associated with multiple chronic diseases. Currently, high‐dose liraglutide has been used for weight control in non‐diabetic patients. Considering incretin‐based therapy is more effective in Asian populations, the effect of low‐dose liraglutide in weight control among these non‐diabetic groups has not been well evaluated. Our study aimed to evaluate the efficacy of low‐dose liraglutide in weight control among Taiwan patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…There is some evidence of differences in the efficacy of incretin-based therapy between Asian and non-Asian populations [ 36 ]; however, because the majority (90.2%) of patients in the SURE UK study were white, it was not possible to determine differences in mean outcome change by race.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of differences in the efficacy of incretin-based therapy between Asian and non-Asian populations [ 36 ]; however, because the majority (90.2%) of patients in the SURE UK study were white, it was not possible to determine differences in mean outcome change by race.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, liraglutide has been FDA-approved for chronic weight management of obese adults and children above the age of 12 [ 86 ]. The approved dose for weight loss is a high dose of 3.0 mg and the body weight clearly decreases in a dose-dependent manner [ 87 ]. Given this, any consideration of the treatment of intestinal diseases with GLP-1 agonists would have to carefully consider the therapeutic dose to avoid undesired weight loss.…”
Section: Theoretical Drug Safety Of Glp-1mentioning
confidence: 99%
“…Some studies have evaluated the efficacy of liraglutide for weight reduction in non-diabetic obese people. For example, a retrospective cohort study [ 5 ] evaluated the efficacy of low-dose liraglutide (0.6 vs. 1.2 mg/day) for 12 weeks on body weight among Taiwanese non-diabetic patients. The authors found that among patients in the liraglutide 1.2 mg group, 5.6% reached weight reduction compared to baseline ( p < 0.001), whereas in the 0.6 mg group 6.4% reached weight reduction ( p < 0.001); however, no significant differences in weight reduction were found between the two dose groups (absolute difference 1.2 mg vs. 0.6 mg −0.8%, 95%CI −0.12 to 0.11).…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluated the efficacy at 12 weeks of low-dose liraglutide on the weight of Taiwanese patients without T2D. Compared to baseline, 5.6% of patients in the liraglutide 1.2 mg group reached weight reduction ( p < 0.001), whereas in the 0.6 mg group 6.4% reached weight reduction ( p < 0.001) [ 5 ]. However, there was no difference in weight reduction between liraglutide doses (absolute difference 1.2 mg vs. 0.6 mg −0.8%, 95%CI −0.12 to 0.11).…”
Section: Introductionmentioning
confidence: 99%